THE ONTOLOGICAL AND SOCIAL-PHILOSOPHICAL DIMENSIONS OF IMMIGRANT ADAPTATION: A DIALECTIC OF IDENTITY AND ALTERITY (World Conference on Social Sciences, Law and Public Policy, 2026)
This article explores the multifaceted process of immigrant adaptation through a socio-philosophical lens. Moving beyond mere sociological statistics, it examines the ontological crisis of displacement, the transformation of the "Life-world" (Lebenswelt), and the ethical encounter with the "Other." Drawing upon the phenomenological insights of Alfred Schütz and the ethical frameworks of Emmanuel Levinas, the study analyzes how the immigrant navigates the tension between their cultural heritage and the new social reality. The research concludes that adaptation is not a linear assimilation but a dialectical synthesis that creates a "Third Space" of identity.
Keywords: Immigrant adaptation, Social Philosophy, Alterity, Phenomenology, Identity, The Stranger, Life-world, Ontological security.